Language Maintenance of Banjarese among Students of the State Polytechnic of Tanah Laut - Ningsih, Y (KnE Social Sciences, 2018)
Banjarese is a traditional language that has special characteristics for the speaker and has becomes a symbol of the identity of indigenous people of South Kalimantan, especially those that develop from generation to generation as their local languages. Therefore they keep the identity of Banjarese. The phenomena of other local languages development in the State Polytechnic of Tanah Laut is the background of this research. The development would have an impact on the interaction between other students (using other language) and local students (using Banjarese) in the State Polytechnic of Tanah Laut. The problem in this study is concerned with factors influencing the preservation of Banjarese among students of the State Polytechnic of Tanah Laut. The presentation of the data described in qualitative descriptive method and this study conducted through field survey with interviews and observations. The findings revealed that the preservation of Banjarese was still very good (maintained by students), the possibility of a language shift was still relatively small. Other factors are the language status of Banjarese as the mother tongue as well as the identity of Banjar ethnic, the pride of the culture, the activity in college, the numbers of Banjarese user, and solidarity among students. This is because the students of the State Polytechnic of Tanah Laut consistently used Banjarese according to the situation and condition. Keywords: language maintenance, Banjarese, students